Acoustic effects on binary aeroelasticity model - Kok, Hwa Yu; Djojodihardjo, Harijono; Kadarman, A Halim (Chulalongkorn University, Faculty of Engineering, 2011)

(untitled)
Acoustics is the science concerning the study of sound. The effects of sound on structures attract overwhelm interests and numerous studies were carried out in this particular area. Many of the preliminary investigations show that acoustic pressure produces significant influences on structures such as thin plate, membrane and also highimpedance medium like water (and other similar fluids). Thus, it is useful to investigate structural response to acoustics on aircraft, especially on aircraft '"/ings, tails and control surfaces which are vulnerable to flutter phenomena. The present paper describes the modelling of structure-acoustic interaction to simulate the external acoustic effect on binary flutter model. Here, the model is illustrated as a rectangular wing where the aerodynamic wing model is constructed using strip theory \vith simplified unsteady aerodynan1ics involving the terms for flap and pitch degree of freedom. The external acoustic excitation, on the other hand, is modelled using a four-node quadrilateral isoparametrlc element via finite element approach. Both equations are then carefully coupled and solved using eigenvalue solution. Next the mentioned approach is implemented in MATLAB and the outcome or the simulated results arc later described, analyzed and illustrated.